Emotional intelligence and job stress of agricultural officers of Kerala State Department of Agriculture: a psycho-personal analysis - Reshma A Victor (Department of Agricultural Extension, College of Agriculture, 2018)
The study entitled “Emotional intelligence and job stress of Agricultural Officers of Kerala State Department of Agriculture: A psycho–personal analysis” was conducted from 2016 – 2018 to study the emotional intelligence and job stress of Agricultural Officers of Kerala State Department of Agriculture and analyze the factors which influence emotional intelligence and job stress. Constraints experienced by the Agricultural Officers and the profile characteristics were also be studied. The study was undertaken in the three districts of Kerala viz., Kasaragod from North, Thrissur from Central and Thiruvananthapuram from South Kerala. From each district, 30 Agricultural Officers (15 female and 15 male) were randomly selected using simple random sampling. The total sample size was 90. A structured interview schedule was prepared for data collection. Frequency, percentage analysis, mean, standard deviation, simple correlation, Kruskal - Wallis test, Mann - Whitney U test and factor analysis were employed in the analysis and interpretation. The study had two dependent variables and 13 independent variables. The dependent variables were emotional intelligence and job stress. Emotional intelligence was measured by using the scale developed by Goleman (1995) with 5 sub-components, self awareness, managing emotions, motivating oneself, empathy and social skill. The job stress was assessed by using the scale developed by Shrivastav and Singh (1981) with 12 sub-components, role overload, role ambiguity, role conflict, group and political pressures, responsibility for persons, under participation, powerlessness, poor peer relation, intrinsic impoverishment, low status, strenuous working conditions and unprofitability. Based on the analysis of data, it was revealed that majority (76.67%) of the respondents were having medium emotional intelligence in three district. Using Kruskal - Wallis it was found that there was no significant difference between emotional intelligence in the three districts. The study found that, majority (60%) of the respondents were having medium job stress. There was significant difference in job stress among the three districts. Using factor analysis it was observed that out of the 12 components role overload, role ambiguity, role conflict, group and political pressures, under participation, powerlessness and strenuous working conditions were the major contributors to the job stress. Most (43.33%) of the respondents belonged to the age category of 35-45 years. More than half (76.67%) of the respondents were married and more than half (54.44%) of the respondents had Bachelor’s degree only. More than half (61.11%) of the respondents were having 4-5 members in their family. It was also found that 48.89 per cent of the respondents were having 10-20 years of job experience. Majority (92.22%) of the respondents opined that they have very low promotional opportunities. Majority of the respondents had medium level of attitude towards profession (72.22%), self confidence (72.22%), perceived workload (65.56%), Political orientation (78.89%), leadership quality (74.44%) and organizational climate (78.89%). Regarding the distance from work place, less than half (44.44%) of the respondents had to travel 10-20 km to the place of work. The factors which influenced emotional intelligence were self confidence and leadership quality. Job experience, attitude towards profession, self confidence, leadership quality and organizational climate were the main factors which influenced job stress. The major constraints faced by the respondents were excessive workload, lack of promotional opportunities, lack of proper training schedule of the officer, lack of suitability of different schemes and its implementation in different localities and political interference in day to day activity. Thus, the study revealed that majority of the respondents were having medium level of emotional intelligence and job stress. Three districts had no significant difference regarding emotional intelligence whereas there was significant difference in the case of job stress. The constraints faced by the respondents need attention from the policy makers and government for improving the performance of the Agricultural Officers.